Three-dimensional surgical planning and clinical evaluation of the efficacy of distal tibial tuberosity high tibial osteotomy in obese patients with varus knee osteoarthritis. (January 2022) - Huang, Ye; Tan, Yetong; Tian, Xiangdong; Wang, Jian; Zhu, Guangyu; Wang, Rongtian; Xue, Zhipeng; Ma, Sheng; Hu, Yuanyi; Ding, Tiansong
Highlights: Distal tibial tuberosity high tibial osteotomy (DTT-HTO) can effectively correct varus deformity, and relieve symptoms. DTT-HTO has a significant curative effect in obese patients with varus knee osteoarthritis. A new patented π-shaped plate using DTT-HTO in obese patients with varus knee osteoarthritis is proposed. The π-shaped plate can effectively prevent angle loss and internal fixation fractures due to its high levels of strength and stability. Three-dimensional surgical planning using DTT-HTO helps us to accurate preoperative evaluation, optimize osteotomy and improve the successful rate. Abstract: Purpose: High tibial osteotomy (HTO) is an effective surgical treatment for varus knee osteoarthritis. However, obese patients require reinforced internal fixation materials to prevent internal fixation fractures and hardware failure after osteotomy. Therefore, the purpose of our study is to evaluate the clinical efficacy of distal tibial tuberosity high tibial osteotomy (DTT-HTO) using the new patented π-shaped plate in obese patients with varus knee osteoarthritis. Method: Thirty-four obese patients (39 knees) with varus knee osteoarthritis who underwent DTT-HTO with the π-shaped plate and second-look arthroscopy when implant removal occurred from September 2017 to June 2020 were retrospectively reviewed. Three-dimensional surgical planning using DTT-HTO on the knees is performed. There were 9 males and 25 females, with body mass index (BMI) values ranging from 30.3 to 38.5 kg/m 2 and ages ranging from 50 to 75 years old. The radiological assessment was performed with the femora tibial angle (FTA) and the weight-bearing line ratio (WBLR). The clinical outcomes were evaluated by the Hospital for Special Surgery (HSS) knee score and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The status of the cartilage was evaluated by the International Cartilage Repair Society (ICRS) grading system. Results: All patients were followed up for 18-30 months. The FTA significantly changed from 181.68±1.68 . preoperatively to171.29±1.51 . at the last follow-up (P<0.001). The WBLR significantly increased from 16.85±2.20 to 55.41±2.46% from before surgery to the last follow-up after surgery (P<0.001). The HSS score significantly improved from 56.65±5.27 preoperatively to 68.79±2.61, 77.82±2.15, and 86.12±2.78 at the 6-month, 12-month, and last follow-up after surgery (P<0.001). The WOMAC score significantly decreased from 105.47±3.89 preoperatively to 80.50±4.20, 71.44±4.65, and 52.44±3.14 at the 6-month, 12-month, and last follow-up after surgery (P<0.001). During implant removal, no internal fixation fractures occurred in any patient. The articular cartilage grade in the medial compartment of the knee were significantly higher in the second arthroscopy than in the first arthroscopy, according to the ICRS grading system (P<0.001). The articular cartilage grade in the lateral compartment of the knee showed no statistical differences from the first- to the second-look arthroscopy (P>0.05). Conclusion: There are no correlation between BMI and postoperative outcomes. DTT-HTO shows yield excellent clinical results in obese patients with varus knee osteoarthritis. It can be recommended to be used for the heavy patients.